2006
DOI: 10.1080/j157v06n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Mechanistic Studies on the Smooth Muscle Relaxant Effect of Hydroalcoholic Extract ofCurcuma caesia

Abstract: The extract showed a dose-dependent, non-specific relaxation of pre-contracted isolated guinea pig trachea. The non-specific relaxant effect of the extract may be due to its ability to modulate calcium activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…(black turmeric) is a perennial herb with bluish black rhizomes and one of the endangered species amongst the medicinal plants found in Manipur. [ 13 ] Many of the researches worked on it like anti-fungal activity,[ 14 ] smooth muscle relaxant and anti-asthmatic activity,[ 15 ] bronchodilating activity,[ 16 ] antioxidant activity,[ 17 ] anxiolytic and central nervous system depressant activity, locomotor depressant, anti-convulsant,[ 18 ] anthelmintic activity,[ 19 ] anti-bacterial activity,[ 20 ] and anti-ulcer activity. [ 21 ] Methanolic extract of the rhizome of Curcuma caesia Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…(black turmeric) is a perennial herb with bluish black rhizomes and one of the endangered species amongst the medicinal plants found in Manipur. [ 13 ] Many of the researches worked on it like anti-fungal activity,[ 14 ] smooth muscle relaxant and anti-asthmatic activity,[ 15 ] bronchodilating activity,[ 16 ] antioxidant activity,[ 17 ] anxiolytic and central nervous system depressant activity, locomotor depressant, anti-convulsant,[ 18 ] anthelmintic activity,[ 19 ] anti-bacterial activity,[ 20 ] and anti-ulcer activity. [ 21 ] Methanolic extract of the rhizome of Curcuma caesia Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…(black turmeric) is a perennial herb with bluish black rhizomes and it is famous for its medicinal properties. It is recognised as a medicinal herb to possess with various properties such as anti-fungal activity Banerjee and Nigam [16] , smooth muscle relaxant and anti-asthmatic activity Arulmozhi et al [17] , bronchodilating activity Paliwal et al [18] , antioxidant activity Mangla et al [19] , anxiolytic and CNS depressant activity, locomotor depressant, anti-convulsant Karmakar et al [20] , anthelmintic activity Gill et al [21] , anti-bacterial activity Rajamma et al [22] , anti-ulcer activity Das et al [23] . The phytochemical studies of C. caesia revealed the presence of multiple phytoconstituents like essential oils with camphor, ar-turmerone, (Z) ocemene, ar-curcumene,1,8-cineole, elemene, borneol, bornyl acetate, curcumene, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The preliminary mechanistic studies have shown its smooth muscle relaxant activity on hydro alcoholic extract. [6]…”
Section: Introductionmentioning
confidence: 99%